Obstacles to the creation of successful bus rapid transit systems: The case of Bangkok. (December 2016) - Wu, Irene; Pojani, Dorina
Abstract: Bangkok has failed in the implementation of its BRT system. The single line in operation since 2010 stretches only 15 km and transports merely 15, 000 passengers daily. This article examines the reasons why Bangkok has (so far) been unable to implement a full BRT system, unlike many counterparts in Asia, Africa, and Latin America, which have similar financial constraints. The authors' position is that there is as much to learn from failure as from success. BRT issues are placed in the broader context of urban transport problems in Bangkok. The study indicates that the Bangkok BRT project was curtailed due to a combination of reasons, which confirm the findings of prior studies on BRT planning and implementation worldwide. The crucial issues in this case were the weak and discontinued political leadership and the failure to manage competing modes, the primary of which is the automobile. Nonetheless, creating a however limited BRT system was not a loss for Bangkok and extension plans could always be resumed in the future. Should another attempt be made at creating an integrated and large-scale BRT system, local planners and leaders who care about the city's sustainable future must avoid repeating past mistakes and falling into past behavioral patterns. While this article focuses on a single case study, the findings apply to a number of cities in similar geo-political and economic contexts.